Evaluasi Usulan Pembangunan Terminal Baru Bandar Udara H.A.S. Hanandjoeddin Tanjung Pandan - Zulaichah Zulaichah (Research and Development Agency of The Ministry of Transportation, 2015)
Belitung is one of the districts in the province of Bangka Belitung islands. This district has the advantage in the field of processing industry and tourism. The Regent of Bangka Belitung District proposes the construction of a new terminal in H.AS. Hanandjoeddin Airport to improve passenger service. The assessment aims to determine whether the construction of the new terminal is already required at the H.AS Hanandjoeddin airport. The method used in the study was descriptive analysis. Based on study results, the construction of the new terminal should be carried out with the consideration that the current capacity of the passenger terminal is not able to accommodate the number of passengers during rush hour (IAP4 landside = 4.39). Beside that, there is land availability for the new terminal area. Furthermore, Belitung has a high tourism potential. It requires reliable air transportation to accelerate the pace of economic growth and development of the tourism sector. Keywords: Hananjoeddin, passenger terminal, capacity. Kabupaten Belitung adalah salah satu kabupaten di provinsi Bangka Belitung. Kabupaten ini memiliki keunggulan di bidang industri pengolahan dan pariwisata. Bupati Kabupaten Belitung mengusulkan pembangunan terminal baru untuk meningkatkan pelayanan penumpang. Pengkajian bertujuan untuk mengetahui apakah pembangunan terminal baru sudah diperlukan di Bandara H.AS. hanandjoeddin. Metode yang digunakan dalam pengkajian adalah analisis deskriptif. Berdasarkan hasil kajian, pembangunan terminal baru perlu dilaksanakan dengan pertimbangan bahwa kapasitas terminal penumpang saat ini sudah tidak mampu menampung jumlah penumpang pada jam sibuk (IAP4 sisi darat = 4,39) dan lahan untuk area terminal baru sudah tersedia. Selanjutnya Kabupaten Belitung memiliki potensi pariwisata yang tinggi. Hal tersebut memerlukan sarana transportasi udara yang handal untuk mempercepat laju pertumbuhan ekonomi dan pembangunan sektor pariwisata. Kata kunci: Hananjoeddin, terminal penumpang, kapasitas.